Agrilus Curtis (Coleoptera: Buprestidae) of the Baja California peninsula, México - Hespenheide, Henry A.; Westcott, Richard L.; Bellamy, Charles L. (Zootaxa, 2011)
The genus Agrilus Curtis 1825 is reviewed for the Baja California peninsula of Mexico. Of the 25 species included, 11 are recorded here for the first time and four are previously unknown to science and described as new: Agrilus barri new species, A. interstitialis new species, A. vescivittatus new species, and A. argythamniae new species. Four additional species may be expected based on their occurrence just north of the border in the United States. Upon further study Agrilus auroguttatus Schaeffer 1905, revalidated status, is judged to be a separate species from A. coxalis Waterhouse 1889. Figures and a key to known and expected species are given, as well as a summary checklist.